The Making of a Teenage Service Class : Poverty and Mobility in an American City - Ray, Ranita, 1983- (Book collections on Project MUSE., 2018)
"Stereotypes of economically marginalized black and brown youth focus on drugs, gangs, violence, and teen parenthood. Families, schools, nonprofit organizations, and institutions in poor urban neighborhoods emphasize preventing such "risk behaviors." In The Making of a Teenage Service Class, Ranita Ray uncovers the pernicious consequences of concentrating on risk behaviors as key to targeting poverty. Having spent three years among sixteen black and Latina/o youth, Ray shares their stories of trying to beat the odds of living in poverty. Their struggles of hunger, homelessness, and untreated illnesses are juxtaposed with the perseverance of completing homework, finding jobs, and spending long hours traveling from work to school to home. By focusing on the lives of youth who largely avoid drugs, gangs, violence, and teen parenthood, the book challenges the idea that targeting these "risk behaviors" is key to breaking the cycle of poverty. Ray compellingly demonstrates how the disproportionate emphasis on risk behaviors reinforces class and race hierarchies and diverts resources that could support marginalized youth's basic necessities and educational and occupational goals."--Provided by publisher